The all‐ceramic, inlay supported fixed partial denture. Part 5. Extended finite element analysis validation. (December 2013) - Thompson, MC; Zhang, Z; Field, CJ; Li, Q; Swain, MV
Abstract Background This study is the last in a series detailing an investigation into the all‐ceramic, inlay supported fixed partial denture, the major concern of which has been the examination of the stress responses of the bridge via the use of finite element analysis (FEA) and its validation. The progression from a classic FEA to the current extended or enriched FEA (XFEA) will be described and the validation performed. Methods XFEA modelling was compared and validated against the experimental model analysis (EMA) as described in a previous study. Results The two EMA load case fracture strengths of 160 N and 313 N compared favourably with the best two fracture predictions from the XFEA of 185 N and 213 N (maximum principal stress criterion) respectively, with the origin of fracture and overall trajectory and pattern of crack propagation agreeing very well. Conclusions XFEA load prediction is within 15% of the EMA in the best case. The sensitivity of the bridges to loading position variations was accurately predicted by the XFEA, together with the change in fracture origin from the molar to premolar embrasures. With this, the authors believe that they have provided a convincing validation, both qualitatively and quantitatively, of an anatomically realistic dental bridge.